1991
DOI: 10.1111/j.1523-1739.1991.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Consequences of Ecosystem Fragmentation: A Review

Abstract: Abstrack Resemcb on fragmented ecosystems bas focused mostly on tbe biogeograpbic consequences of tbe creation of habitat "islands" of d i f f m t s i z e and bas p v f d e d little of practical value to managers H o m , ecosystem fragmentation causes large changes in tbepbysfcal environment as well as biogeograpbic changes Fragmentation generally msults in a landscape that consists of remnant areas of native vegetation surrounded by a mdrlx of agricultural or otber developed land As a mu14 fluxes of radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
2,121
5
273

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,437 publications
(2,420 citation statements)
references
References 99 publications
21
2,121
5
273
Order By: Relevance
“…Levin and Paine, 1974;Steele, 1978;Paine and Levin, 1981;Sousa, 1984;. It is in terrestrial environments, however, that the quantification of landscape pattern and the study of the effect of pattern on ecological processes have made significant advances in understanding animal movement and persistence, the effects of disturbance, the importance of broad-scale environmental change and the design of resource management strategies (Turner, 1989;Saunders et al, 1991;Hobbs, 1994;Forman, 1995;Farina, 1998). Landscape ecology principles and tools are applicable throughout ecology and recent reviews have outlined the usefulness of a landscape ecology approach for the marine environment (Kneib, 1994;Robbins and Bell, 1994;Bell et al, 1997;Irlandi and Crawford, 1997;Eggleston, 1999).…”
Section: Spatial Hierarchymentioning
confidence: 99%
“…Levin and Paine, 1974;Steele, 1978;Paine and Levin, 1981;Sousa, 1984;. It is in terrestrial environments, however, that the quantification of landscape pattern and the study of the effect of pattern on ecological processes have made significant advances in understanding animal movement and persistence, the effects of disturbance, the importance of broad-scale environmental change and the design of resource management strategies (Turner, 1989;Saunders et al, 1991;Hobbs, 1994;Forman, 1995;Farina, 1998). Landscape ecology principles and tools are applicable throughout ecology and recent reviews have outlined the usefulness of a landscape ecology approach for the marine environment (Kneib, 1994;Robbins and Bell, 1994;Bell et al, 1997;Irlandi and Crawford, 1997;Eggleston, 1999).…”
Section: Spatial Hierarchymentioning
confidence: 99%
“…In highly fragmented landscapes, the decline of wildlife popu¬ lations is greater than that expected by habitat loss alone (Andren, 1994) and ultimately, these changes to the landscape can isolate groups of animals (Belisle & Desrochers, 2002). Habitat fragmentation is consid¬ ered one of the greatest threats to biodiversity mak¬ ing it an important conservation issue (Harris, 1984;Forman & Godron, 1986;Saunders et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…There is 82 considerable evidence that habitat fragmentation can cause declines in avian populations 83 (Bender et al, 1998;Schmiegelow and Monkkonen, 2002). The main reasons of these 84 species' declines are a reduction of habitat areas (area effect) and an increase in distance 85 between remaining habitat patches that influences therefore dispersal ability (isolation 86 effect, Andrén, 1994; Opdam et al, 1994; reviewed in Saunders et al, 1991;Debinski 87 and Holt, 2000). Habitat fragmentation has been suggested to condition song variation in 88 some bird species (white crowned sparrow Zonotrichia leucophrys nuttalli, Trainer,89 1983; corn bunting Miliaria calandra, Holland et al, 1996), but direct evidence has only 90 been shown in the Dupont's lark Chersophilius duponti Tella, 2005, 2007).…”
mentioning
confidence: 99%